Development of Emergency Medical Services Amid 5 Years’ Experience at a Medical School in Thailand - Apiratwarakul, Korakot; Ruamsuk, Phongphat; Suzuki, Takaaki; Celebi, Ismet; Tiamkao, Somsak; Bhudhisawasdi, Vajarabhongsa; Ienghong, Kamonwon (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The development of emergency medical services (EMSs) in Thailand is divided into two phases following the enactment of the Emergency Medical Act in 2007 aimed at making the work model more systematic. However, the amount of EMS operations has not been well studied. AIM: The aim of this study was to describe the pattern of EMS operations throughout a 5-year period. METHODS: A retrospective, single-centered study at a medical school hospital in Thailand. Data were gathered from the EMS database at Srinagarind Hospital throughout the years 2016–2020. RESULTS: A total of 10,384 EMS operations were examined over a 5-year period (2016–2020). The mean age of patients in 2016 was 40.2 ± 3.5 years, and 55.3% (n = 1178) were male. Operations were most commonly performed during the afternoon shift (4.00 p.m.–0.00 a.m.) 41.0%, 38.6%, 39.5%, 39.2%, and 50.8%, respectively. The amount of EMS members had a tendency to increase in number throughout the 5 years of study (p = 0.022). The average times from 1669 center call receipt to arrival on scene (response time) for 2016 and 2020 were 8.52 ± 2.20 min and 5.52 ± 3.02 min, respectively (p < 0.001). CONCLUSION: The development of EMS at Srinagarind Hospital took place with an increase in the age of patients, number of operations in the afternoon shift, and EMS members, yet with a decrease in response times.